ANALISIS FAKTOR-FAKTOR REPEAT ORDER TERHADAP IMPLEMENTASI STRATEGI FLASH SALE PADA USER APLIKASI MARKETPLACE SHOPEE - Supardi; Ayu Lestari (Lembaga Pengembangan Kinerja Dosen, 2022)
The rapid development of e-commerce, coupled with advances in technology, makes the needs of the community increase. In addition, fulfilling needs is also easier with the use of e-commerce applications available on smartphones. Based on this, a fast-growing online shopping culture emerged in the community. Over time, many programs were intensified by e-commers=ce to attract more consumers and increase sales to the company, so that it became a lifestyle for consumers. This research uses a literature study approach by analyzing the topic of repeat orders on the marketplace application with a case study on Shopee. The results of this study found many factors that affect repeat orders on the marketplace application.